1978
DOI: 10.1080/03601237809372093
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term studies on the fate of 3, 4‐dichloroaniline‐14C in a plant‐soil‐system under outdoor conditions

Abstract: 3, 4-dichloroaniline-14 C was applied to soil under outdoor conditions, at a rate corresponding to 1.43 kg/ha. Barley was sown immediately after application; in the following year, potatoes were planted. After the first season, a total of 69.8% of the radiocarbon applied was recovered in soil, plants and leaching water, and after the second year the recovery was still 67.1%. Most of the radioactivity was found in the top soil layer (0-10 cm depth).The total radioactivity in barley grains was 0.02 μg/g (equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In one study, 3,4-dichloroaniline was applied to a German soil, and 46% of the compound remained bound to the soil two years after treatment (26). In a separate study, 83% of 14C-labeled atrazine remained associated with the soil after nine years; 50% of this residue represented bound material (27).…”
Section: Biological Consequences Of Bindingmentioning
confidence: 99%
“…In one study, 3,4-dichloroaniline was applied to a German soil, and 46% of the compound remained bound to the soil two years after treatment (26). In a separate study, 83% of 14C-labeled atrazine remained associated with the soil after nine years; 50% of this residue represented bound material (27).…”
Section: Biological Consequences Of Bindingmentioning
confidence: 99%
“…It has been shown for example that a portion of these residues are bioavailable to plants, 34 ' 52 ' 53 to earthworms 35 ' 53 and also under outdoor conditions. 30 The aniline moiety or its transformation products may be immobilized by physical adsorption and by chemical binding. By model experiments it has been shown that the biological activity is not required for the formation of humus bound complexes, 59 and a portion is also nonhydrolyzable.…”
Section: Bound Residuesmentioning
confidence: 99%
“…4 After application of 3,4-dichloroaniline-14 C, the unchanged parent compound comprised only about 1 % of 14 C recovered in soil; 3,4-dichloroformanilide, 3,4-dichloroacetanilide, 6-hydroxy-3,4-dichloroacetanilide, and 3,3',4,4'-tetrachloroazobenzene were identified as conversion products. 5 Tables 2 and 3 demonstrate the concentrations of soil-bound residues of 14 C-labeled 4-chloroaniline and 2,4,6-trichloroaniline in total extracted soil and in various soil fractions. Additionally, they show aerobic biomineralization, photodegradation, and plant uptake rates of 14 C bound in total soil and in various soil fractions, and of 14 C-reference compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Since total recovery of 14 C was highest in the experiment with 3,4-dichloroaniline-14 C (left column), the absolute amounts of soil-bound 14 C was highest for this experiment also. 5 Radioactivity in soil extracts from the experiments with 4-chloroaniline-14 C and 3,4-dichloroaniline-14 C in lysimeters was separated into parent compounds and conversion products by various chromatographic methods. After application of 4-chloroaniline-14 C, no free unchanged parent compound could be detected; 4-chloroformanilide, 4-chloroacetanilide, 4-chloronitrobenzene, 4-chloronitrosobenzene, 4,4'-dichloroazoxybenzene, and 4,4'-dichloroazobenzene were identified as conversion products.…”
Section: Methodsmentioning
confidence: 99%